Rural-urban and regional variations in aspects of caregiving, support services and caregiver health in the USA: evidence from a national survey - Mary L Greaney; Steven A Cohen; Neelam H Ahmed; Kerri A Ellis; Hayley Lindsey; Caitlin C Nash (BMJ Open)
Objectives Due to substantial regional variability in available caregiving services and supports, culture and health status among informal caregivers in the USA, the study objective was to explore how rural-urban differences in aspects of caregiving—caregiving intensity, distance to care recipient, caregiver burden, caregiver health and caregiving support—vary by US Census region (Northeast, South, Midwest and West) after accounting for other social determinants of health.Design This study was a secondary analysis of multiwave, cross-sectional study data.Setting The data were collected on a representative sample of informal, unpaid caregivers to older adults.Participants A sample of n=3551 informal caregivers from the National Study of Caregiving identified by older adult care recipients from waves 1 (2011) and 5 (2015) of the National Health and Aging Trends Study.Primary and secondary outcome measures Primary outcome measures were caregiving intensity (provided support for/with the number of activities of daily living (ADLs) and instrumental ADL (IADLs)) caregiver assisted with, hours of caregiving per month), caregiver burden (physical, emotional and financial), support services sought (types and total number), caregivers’ self-reported health and health status (individual comorbidities and a total number of comorbidities). Analyses were stratified by US Census region and rural-urban status, as defined by the US Census Bureau, of census tract of caregiver residence.Results Urban caregivers provided higher levels of ADL support in the Northeast (beta=0.19, 95% CI 0.03, 0.35) and West (beta=0.15, 95% CI 0.05,0.26) regions. Urban caregivers provided significantly higher levels of ADL support (p=0.020), IADL support (p=0.033) and total ADLs plus IADLs (p=0.013) than rural caregivers. Caregivers living in the South had higher amounts of monthly hours spent caregiving, ADL support, IADL support and combined ADLs plus IADLs and were more likely to have obesity, report poor or fair health, have heart conditions and experience emotional difficulty from caregiving (all p<0.001).Conclusions Study findings underscore caregiving’s multifaceted and complex nature and identify important urban-rural and regional differences in caregiving in the USA. Healthcare providers and healthcare organisations can have an important role in identifying and mitigating the negative impacts of caregiving on caregivers’ overall health. Interventions and support should be tailored to caregivers’ demographic backgrounds, addressing regional differences.